Wide bandgap donor polymers containing carbonyl groups for efficient non-fullerene polymer solar cells. (February 2021) - Li, Hongneng; Yang, Wenyan; Wang, Wei; Wu, Yao; Wang, Tao; Min, Jie
Abstract: Two wide bandgap conjugated polymers (PTCO8 and PTCO1) with different side chains, composed of alkylcarbonyl-substituted thiophene (TOC) as the electron-withdrawing unit and two-dimension benzodithiophene (BDT) as the electron-donating unit, are developed for non-fullerene polymer solar cells (PSCs). Relative to non-carbonyl-substituted control polymer PTC8, PTCO8 and PTCO1 exhibit a red-shifted absorption and deeper-lying highest occupied molecular orbital (HOMO) level. When blended with ITIC, the as-cast PTCO1-based devices yield a power conversion efficiency of up to 9.33% with an open-circuit voltage of 0.95 V, a short-circuit current density of 16.91 mA cm −2, and a fill factor of 57.9%, outperforming those of PTC8-based devices (4.04%) and PTCO8-based devices (5.91%). This work demonstrates that the carbonyl group is a promising electron-deficient moiety to construct wide-bandgap polymers for non-fullerene PSCs. Adjusting the length of side chains is a feasible strategy to improve PSC performance further. Graphical abstract: Alkylcarbonyl-substituted thiophene is a suitable electron-deficient unit to construct wide bandgap copolymers, and tuning the length of the side chains is a straightforward design strategy to further improve the solar cell efficiency. Image 1 Highlights: Two new polymer donors (PTCO8 and PTCO1) with different side chains are designed and reported. PTCO8:ITIC and PTCO1:ITIC based devices showed the PCEs of 5.91% and 9.33%, respectively. Adjusting the length of side chains was observed to enhance the photovoltaic performance.